Dopamine receptors and sleep induction in man. Issue 5 (May 1979) - Bassi, S; Albizzati, M G; Frattola, L; Passerini, D; Trabucchi, M
Abstract : Sleep induction has been studied in humans after the administration of apomorphine, a direct stimulant of the central dopaminergic system. The drug induced sleep and vomiting in healthy volunteers while it had no significant effect on 10 Parkinsonism patients treated for a long period with L-dopa. Apomorphine given to a group of Parkinsonism patients not receiving any specific treatment, and with a lower degree of disease severity, induced vomiting and sleep with a pattern similar to that in healthy subjects. A relationship between the dopaminergic system and sleep induction is suggested.